Development and evaluation of a multi-document summarization method focusing on research concepts and their research relationships - Ou, Shiyan (2009)
This paper reports the design and evaluation of a method for summarizing a set of related research abstracts. This summarization method extracts research concepts and their research relationships from different abstracts, integrates the extracted information across abstracts, and presents the integrated information in a Web-based interface to generate a multi-document summary. This study focused on sociology dissertation abstracts, but can be extended to other research abstracts. The summarization method was evaluated in a user study to assess the quality and usefulness of the generated summaries in comparison to a sentence extraction method used in MEAD and a method that extracts only research objective sentences. The evaluation results indicated that the majority of sociology researchers preferred our variable-based summary generated with the use of a taxonomy.